2003
DOI: 10.1179/147842203767789203
|View full text |Cite
|
Sign up to set email alerts
|

Holistic model for atmospheric corrosion Part 1 - Theoretical framework for production, transportation and deposition of marine salts

Abstract: This paper discusses the limitations of parametric modelling of corrosion and presents the case that accurate and exible models of atmospheric corrosion require an 'holistic' approach. In such an approach, the processes controlling corrosion across a wide range of physical scales are modelled. These models are based as much as possible on the processes controlling the phenomena under consideration. Being fundamentally based, these models can be extended outside the data sets from which they are derived. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
108
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 9 publications
6
108
0
2
Order By: Relevance
“…Chloride aggressiveness in marine atmosphere zone has its origin in aerosol production, which can take place either in the surf zone and or in the open sea [9,10]. This mechanism, which is strongly influenced by wind characteristics [11], is more effective in seashore due to the breaking waves movement, which contributes to produce more and larger drops [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloride aggressiveness in marine atmosphere zone has its origin in aerosol production, which can take place either in the surf zone and or in the open sea [9,10]. This mechanism, which is strongly influenced by wind characteristics [11], is more effective in seashore due to the breaking waves movement, which contributes to produce more and larger drops [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, which are focused on atmospheric parameters, show the salinity decay of marine aerosol when being transponed inland [7,9,15]. On the other hand, studies that show the relationship between chloride presence in atmosphere and concrete durability are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that salinity wetting increases salt particles sizes and rainfall removes a great amount of salt aerosol [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The hygroscopicity of chloride salts increases particles size and promotes their deposition. Cole et al (2003b) illustrated that the influence of RH on salt concentration is particularly important within the range of 50-70% due to salt wetting. These authors also observed that the washout effect due to rainfall is more effective at higher RH levels.…”
Section: Introductionmentioning
confidence: 99%